SOCIAL MEDIA APPROACH TO PEACE BUILDING IN KAJURU LOCAL GOVERNMENT - Abduljalil Abdulmumini; Babatunde Joseph AYODELE; Aleyomi Timileyin Paul (International Studies Journal)
This study examines the role of social media in promoting peacebuilding efforts in Kajuru Local Government. It explores the public perception of social media's effectiveness, its role in disseminating information about peacebuilding activities, and the challenges and opportunities associated with its use. The study adopts a qualitative research design, employing in-depth interviews with community leaders, peace advocates, local organizations, and other stakeholders. The research is guided by the Technological Determinism Theory, which posits that technology, including social media, shapes and influences societal behaviour and outcomes. Thematic analysis is used to analyse the interview data, identifying common themes and patterns related to social media's role in peacebuilding. The findings reveal that social media is perceived as a powerful tool for raising awareness, amplifying peacebuilding messages, facilitating dialogue and collaboration, and providing opportunities for innovation. However, challenges such as misinformation and polarization are also acknowledged. The study concludes that to harness the full potential of social media in peacebuilding, it is essential to address issues of misinformation, promote responsible engagement, and enhance digital literacy. Based on the findings, the study recommends developing guidelines and best practices for using social media in peacebuilding efforts, collaborating with social media platforms to prioritize peacebuilding content, investing in digital literacy programs, and fostering partnerships between peacebuilding organizations, social media platforms, and local communities.